2008
DOI: 10.1002/jssc.200700524
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic chromatography with polymeric pseudostationary phases

Abstract: Recent research and development efforts concerning polymeric pseudostationary phases (PSPs) for electrokinetic chromatography are reviewed. The introduction of new materials, characterization of structural effects on performance and selectivity, applications, and the use of polymeric PSPs with mass spectrometric detection are considered. Very interesting results concerning the effects of polymer structure have been reported. Significant developments have also been reported in the development of novel applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Several reviews have been dedicated to the use of various chiral surfactants such as molecular micelles [ 18 , 19 , 20 , 21 , 22 ] and glycosidic surfactants [ 23 ]. However, a Scopus search revealed that no reviews were made for bile salts since the review by Otsuka and Terabe two decades ago [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have been dedicated to the use of various chiral surfactants such as molecular micelles [ 18 , 19 , 20 , 21 , 22 ] and glycosidic surfactants [ 23 ]. However, a Scopus search revealed that no reviews were made for bile salts since the review by Otsuka and Terabe two decades ago [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…EKC with the use of polymers as a pseudostationary phase with a large variety of chemical structures can be used to improve the selectivity or performance [18].…”
Section: Introductionmentioning
confidence: 99%
“…Also included are the developments in the use of polymeric nanoparticles as PSPs since 2004, the last time this was reviewed in this series 14. Additional reviews of the developments in polymeric and nanoparticle PSPs have appeared during the current review period 16–19.…”
Section: Introductionmentioning
confidence: 99%